Tranexamic Acid: An Exceedingly Rare Cause of Anaphylaxis during Anaesthesia - R. A. Bansal; A. Nicholas; A. S. Bansal (Case Reports in Immunology)
Tranexamic acid (TXA) allergy is extremely rare. An 80-year-old woman without prior exposure to TXA underwent elective knee replacement. Shortly after induction of anaesthesia and intravenous TXA, she developed hypotension, tachycardia, and facial erythema accompanied by a raised serum tryptase. Later, skin prick and intradermal testing confirmed positive responses to TXA in high dilution and with negative results to the other drugs used. While neuromuscular blocking agents, opiates, and antibiotics remain the most frequent cause of anaphylaxis during anaesthesia, allergy to TXA should always be borne in mind and requires skin testing for confirmation as there are presently no blood tests available.